A33 DOES PREGNANCY ADVERSELY IMPACT THE HEALTH-RELATED QUALITY OF LIFE AMONG WOMEN WITH IBD?. (1st March 2018) - Rodriguez, N; Ambrosio, L; Sutton, R T; Dieleman, L A; Halloran, B P; Kroeker, K I; Peerani, F; Wong, K; Fedorak, R; Huang, V
Abstract: Background: Women with Inflammatory Bowel Disease (IBD) are at risk of flaring during pregnancy, and are associated with adverse maternal and neonatal outcomes. In addition, active IBD has been associated with poor health related quality of life (HRQoL). However, whether pregnancy-related changes also influence HRQoL of life is still unknown. Aims: To assess the impact of pregnancy on the health related quality of life (HRQoL) among women with IBD and the impact of IBD disease activity on HRQoL in pregnant women with IBD. Methods: Adult (≧18years) women with Crohn's disease (CD) or ulcerative colitis (UC), and healthy volunteers who were either preconception or pregnant participated in a quality of life research study, and followed until delivery. Participants completed disease activity indices, such as Harvey Bradshaw Index (HBI) for CD or partial Mayo score (pMayo) for UC. Clinically active disease was defined as mHBI ≧5 or pMayo ≧2; whereas c-reactive protein ≧8.0mg/L and fecal calprotectin ≧250mg/kg indicated objectively active disease. Short IBD quality of life (SIBDQ) survey was administered at each time point (preconception, trimester 1, trimester 2, and trimester 3) and compared between groups for diagnosis and disease activity. SIBDQ scores in each time point were compared using independent samples median t-test and differences between categorical variables were analyzed using chi-square test. Statistically significant results were considered to have p <0.05. All statistical analyses were performed using SPSS statistical program, version 24.0. Results: A total of 70 women completed at least one SIBDQ survey during the follow up period. There were 11 (15.7%) healthy volunteers, 36 (52.4%) women with UC, and 23 (32.9%) women with CD. There was no difference in SIBDQ scores at preconception or during pregnancy between healthy women and women with IBD. SIBDQ scores were lower in IBD patients than in healthy participants in trimester 2 of pregnancy. Furthermore, SIBDQ scores were significantly lower in patients who had clinically active disease in trimesters 2 and 3. No statistically significant differences were found when patients were grouped by objective disease activity. Conclusions: Overall, HRQoL was reduced in women with IBD and especially during clinically active disease during pregnancy. Women with inactive IBD during pregnancy have similar IBD related quality of life as women without IBD. Our findings encourage further research on the interaction of IBD and pregnancy to improve patient and physician related knowledge in optimizing pregnancy outcomes in IBD patients. Funding Agencies: WCHRI, CEGIIR, University of Alberta Faculty of Medicine